Israliyat dalan Tafsir Al-Qur’an - Ivan Riky Hardiansyah; Ulil Azmi; Saskia Amanda Putri; Riska Sawitri (Indo Publishing, 2026)
Israiliyat is one of the elements frequently found in classical qur’anic exegesis literature. Its presence is closely related to the interaction between muslims and jewish-christian traditions, especially during the early period of islamic development. This study aims to examine the nature of israiliyat, its sources, and how exegetes respond to it in interpreting the qur’an. The method used is a library research approach with descriptive-analytical analysis of classical and contemporary tafsir works. The findings indicate that israiliyat can be categorized into three types: those consistent with islamic teachings, those that contradict them, and those whose authenticity is uncertain. Scholars have shown diverse attitudes, ranging from selective acceptance to total rejection. This study highlights the importance of a critical approach in dealing with israiliyat to avoid distortion in understanding the qur’an.